Relationship between competitive aggressiveness on performance of commercial state corporations in Kenya (African Journal of Science, Technology and Social Sciences, 2022)
This study sought determine influence of Competitive Aggressiveness on performance of commercial State Corporations in Kenya. The study was guided by Resource-Based Theory. the study used a positivism research philosophy. The research study used descriptive research designs which was guided by hypothesis and focused on the frequency with which something occurs or the relationship between variables. The target respondents were three Managers from any department (finance, HR, administration or marketing) within the commercial state corporation. Therefore, the target population was 165 respondents from 55 commercial state corporations in Kenya. The study adopted a census of all the 55 commercial state corporations. The study collected both primary and secondary data and utilize both qualitative and quantitative data. Statistical Package for Social Scientists (SPSS) was used to help in data analysis. Simple linear regression model, and multiple linear regression model were used to assess the relationship between the study variables. From the results of the analysis the study concluded that and competitive aggressiveness influences both financial and non-financial performance of commercial state corporations. The study identifies that organizational structure moderates the relationship between intrapreneurship and performance. The study recommended that commercial state corporations should embrace intrapreneurship. Further managements of commercial state corporations should understand dimensions of intrapreneurship.
Keywords: Competitive Aggressiveness; Intrapreneurship